Simple fecal flotation is a superior alternative to guadruple Kato Katz smear examination for the detection of hookworm eggs in human stool. - Tawin Inpankaew; Fabian Schär; Virak Khieu; Sinuon Muth; Anders Dalsgaard; Hanspeter Marti; Rebecca J Traub; Peter Odermatt (Public Library of Science (PLoS), 2014)
BACKGROUND:Microscopy-based identification of eggs in stool offers simple, reliable and economical options for assessing the prevalence and intensity of hookworm infections, and for monitoring the success of helminth control programs. This study was conducted to evaluate and compare the diagnostic parameters of the Kato-Katz (KK) and simple sodium nitrate flotation technique (SNF) in terms of detection and quantification of hookworm eggs, with PCR as an additional reference test in stool, collected as part of a baseline cross-sectional study in Cambodia. METHODS/PRINCIPLE FINDINGS:Fecal samples collected from 205 people in Dong village, Rovieng district, Preah Vihear province, Cambodia were subjected to KK, SNF and PCR for the detection (and in case of microscopy-based methods, quantification) of hookworm eggs in stool. The prevalence of hookworm detected using a combination of three techniques (gold standard) was 61.0%. PCR displayed a highest sensitivity for hookworm detection (92.0%) followed by SNF (44.0%) and quadruple KK smears (36.0%) compared to the gold standard. The overall eggs per gram feces from SNF tended to be higher than for quadruple KK and the SNF proved superior for detecting low egg burdens. CONCLUSION/SIGNIFICANCE:As a reference, PCR demonstrated the higher sensitivity compared to SNF and the quadruple KK method for detection of hookworm in human stool. For microscopic-based quantification, a single SNF proved superior to the quadruple KK for the detection of hookworm eggs in stool, in particular for low egg burdens. In addition, the SNF is cost-effective and easily accessible in resource poor countries.